2001
DOI: 10.1007/s11664-001-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of dislocation reduction in GaN using an intermediate temperature interlayer

Abstract: Abstract:A dramatic reduction of the dislocation density in GaN was obtained by insertion of a single thin interlayer grown at an intermediate temperature (IT-IL) after the initial growth at high temperature. A description of the growth process is presented with characterization results aimed at understanding the mechanisms of reduction in dislocation density. A large percentage of the threading dislocations present in the first GaN epilayer are found to bend near the interlayer and do not propagate into the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The samples under study are (11 22)-oriented (Ga, Al)N thick layers grown by either MOVPE or plasma-assisted MBE (series 1), (11 22)-oriented MOVPE GaN layers where two Si x N y interlayers were deposited (series 2), and MBE layers deposited on top of (11 22)-oriented MOVPE GaN templates (series 3). The Si x N y interlayers were inserted directly on the sapphire substrate and after ∼500 nm of GaN growth in an attempt to reduce the defect density [29,30]. Crosssectional and plan-view samples were prepared by mechanical polishing followed by ion milling at 3 kV.…”
Section: Methodsmentioning
confidence: 99%
“…The samples under study are (11 22)-oriented (Ga, Al)N thick layers grown by either MOVPE or plasma-assisted MBE (series 1), (11 22)-oriented MOVPE GaN layers where two Si x N y interlayers were deposited (series 2), and MBE layers deposited on top of (11 22)-oriented MOVPE GaN templates (series 3). The Si x N y interlayers were inserted directly on the sapphire substrate and after ∼500 nm of GaN growth in an attempt to reduce the defect density [29,30]. Crosssectional and plan-view samples were prepared by mechanical polishing followed by ion milling at 3 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the interaction of microstructure defects with certain microstructure features, several approaches were developed that improve the quality of GaN layers by deflecting threading dislocations from the 001 ½ direction. Bourret-Courchesne et al 17 have shown that the TD density in GaN layers can be reduced by a GaN interlayer deposited at an intermediate temperature. This interlayer forces the TDs to bend in the vicinity of the interface between the interlayer and the underlying GaN and consequently helps to reduce their density.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method of defect reduction, which does not require a mask patterning step, is the use of interlayers. 15,16 Specifically, ScN interlayers have been shown to reduce the defect density in c-plane layers to 3 ϫ 10 7 cm −2 ͑Refs. 17 and 18͒ which is comparable to defect densities achieved using ELOG.…”
mentioning
confidence: 99%